2017
DOI: 10.1039/c7cy00129k
|View full text |Cite
|
Sign up to set email alerts
|

New insights into catalyst deactivation and product distribution of zeolites in the methanol-to-hydrocarbons (MTH) reaction with methanol and dimethyl ether feeds

Abstract: The ability of a zeolitic catalyst to dehydrate methanol to dimethyl ether affects catalyst deactivation and product distribution during the methanol-to-hydrocarbons (MTH) reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
136
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(155 citation statements)
references
References 75 publications
19
136
0
Order By: Relevance
“…Furthermore, previous mechanistic studies point to a reaction between sorbed species as the rate‐determining step of both hydrogen‐transfer reactions (leading to the first C−C bond formation; i.e. to initiation of the MTH reaction) and alkene/arene methylation reactions (the propagation reactions of the dual‐cycle MTH mechanism) . The rate of such reactions generally increases upon increasing the coverage of the active site, which is, in this case, induced by a higher acid strength.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, previous mechanistic studies point to a reaction between sorbed species as the rate‐determining step of both hydrogen‐transfer reactions (leading to the first C−C bond formation; i.e. to initiation of the MTH reaction) and alkene/arene methylation reactions (the propagation reactions of the dual‐cycle MTH mechanism) . The rate of such reactions generally increases upon increasing the coverage of the active site, which is, in this case, induced by a higher acid strength.…”
Section: Resultsmentioning
confidence: 97%
“…Recently, however, studies in which methanol and DME were compared as methylating agents of benzene and isobutene, mainly over H‐ZSM‐5, yielded new insight into these reactions. Briefly, the studies revealed a key role of methanol and DME as hydrogen‐transfer agents between the alkene and arene cycles, as well as between monocyclic arenes and heavier analogues . Furthermore, hydrogen‐transfer reactions were found to take place at the Brønsted acid sites, whereas isolated Lewis acid sites had negligible activity for both the methylation and hydrogen‐transfer reactions .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forester and Hower indicated that DTH reaction required less activation energy to proceed as compared with MTH. Martinez‐Espin et al . have compared DTH vs. MTH a variety of catalyst (including H‐ZSM‐5 zeolite) concluding that the former has the following benefits compared with the latter: higher activity, lower yield of aromatics and ethylene (normally regarded as a secondary interest product) and slower deactivation.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] Coke formation has also been attributed to the presence of formaldehyde molecules, formed by hydrogen transfer reactions between methanol molecules, and an increase of the catalyst time life has been found when using dimethyl ether as reactant instead of methanol. 13,21 Since the fast deactivation is the main drawback of SAPO materials as catalysts for the MTO transformation, great efforts have been devoted to the optimization of the physicochemical properties of SAPO-34 in order to improve its catalytic performance. 4,[22][23][24][25][26] Extensive studies indicate that there are some key parameters to be controlled in order to improve the properties of SAPO materials as MTO catalysts.…”
Section: Introductionmentioning
confidence: 99%